Complexity, transdisciplinarity and eco-forming in bringing rural schools closer to life in the countryside and global demands - Cristina Pereira Vieira de Liz; Marlene Zwierewicz; Juan Miguel González Velasco (Universidade Federal do Norte do Tocantins, 2020)
Rural schools are institutions that primarily serve students residing in rural areas. Therefore, they raise pedagogical practices articulated to the demands of local contexts, without disregarding, however, global demands. Considering these demands, this article aimed to analyze Brazilian publications that discuss rural schools and pedagogical practices articulately and suggest an approach with complexity, transdisciplinarity and ecoformation. Through a bibliographic search centered on the qualitative approach, seven publications were identified between the years 2007 and 2019, including scientific articles and works of conclusion of undergraduate and graduate courses. It was observed that the publications approach the triad when they value the articulation of rural schools to rural life, although the global demands and the three concepts are explicitly and intentionally demarcated only in one of the publications.